The Illusionist and the Deluded:: The Business Cycle Demystified from an Entrepreneurial Perspective - Apăvaloaei, Matei (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The aim of this paper is to bring to the attention of the academic community a new line of research focusing on the role played by the ultimate decision maker that activates in the political arena, i.e. the political entrepreneur. This analysis is going to elaborate on the component parts of the income received by the political entrepreneur, starting from the catallactic split of the distinctive economic functions he performs. This approach can aid economists in fine-tuning their understanding of the state, the individual that stands behind this institution, and of the elements that underlie public policy decisions.